2008
DOI: 10.12693/aphyspola.114.423
|View full text |Cite
|
Sign up to set email alerts
|

Structural Study of Polyethylene/Montmorillonite Systems

Abstract: The effect of modification of montmorillonite (with 3-aminopropyltrimethoxysilane or hexadecyltrimethylammonium chloride) on the mechanical properties of the composites based on HDPE Hostalen ACP 5831 with the modified montmorillonite as filler, was studied. The structures of the fillers and nanocomposites were characterised by the scanning electron microscopy and X-ray diffraction study. The effect of the filler modification on the mechanical parameters of the nanocomposites and their structure was assessed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…As the particle size increases, the mechanical properties of the polymer material decrease and therefore it is emphasized that the importance of using smaller particle sized nano-additives and fillers to nanomaterials. These materials which are called polymer nanocomposite, the particles are spread in more homogeneous form because of the nanoscale size of particles in the polymer matrix and better holding can be achieved as the surface area is increased [5,6]. Several studies have been carried out to improve the mechanical and thermal properties of the polymer matrix adding nanoparticles with suitable compatibilizer [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the particle size increases, the mechanical properties of the polymer material decrease and therefore it is emphasized that the importance of using smaller particle sized nano-additives and fillers to nanomaterials. These materials which are called polymer nanocomposite, the particles are spread in more homogeneous form because of the nanoscale size of particles in the polymer matrix and better holding can be achieved as the surface area is increased [5,6]. Several studies have been carried out to improve the mechanical and thermal properties of the polymer matrix adding nanoparticles with suitable compatibilizer [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…These materials which are called polymer nanocomposite, the particles are spread in more homogeneous form because of the nanoscale size of particles in the polymer matrix and better holding can be achieved as the surface area is increased [5,6]. Several studies have been carried out to improve the mechanical and thermal properties of the polymer matrix adding nanoparticles with suitable compatibilizer [5][6][7][8][9]. It has been observed that the Izod impact resistance is reduced by nanosized particle reinforcement to polymeric materials [8,10].…”
Section: Introductionmentioning
confidence: 99%